Publisher Correction: Integrating chemical and mechanical signals through dynamic coupling between cellular protrusions and pulsed ERK activation - Jr-Ming Yang (Nature Portfolio, 2019)
In the original version of this Article, the label “RTK” in Figure 6a was inadvertently changed to “RTE”. This has now been corrected in the PDF and HTML versions of the Article.